Optimizing Business Model Canvas and SWOT for Enhancing Performance and Sustainability in Sharia Cooperatives - Jaka Isgiyarta; Chaidir Iswanaji; Budi Hartono; Supanji Setiyawan; Erni Puji Astutik (Universitas KH. Abdul Chalim Mojokerto, 2025)
The application of the Business Model Canvas (BMC) in the context of Shariah Cooperatives becomes imperative to formulate and evaluate effective business models. BMC provides a clear framework for identifying the key elements of a business model, including customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures. This research aims to explore the application of BMC in Shariah Cooperatives, with a focus on Baitul Maal wat Tamwil (BMT) as a case study. The research method involves Focus Group Discussions (FGDs) with Shariah Cooperative actors and customers to gather in-depth insights regarding the challenges and opportunities faced. The study results show that by using BMC, Shariah Cooperatives can identify and exploit unexplored market opportunities, as well as overcome existing internal weaknesses. Through SWOT analysis, the study also identifies the strengths, weaknesses, opportunities, and threats faced by Shariah Cooperatives, which can be used to formulate more effective development strategies. The findings are expected to provide insights for stakeholders in improving the performance and sustainability of Sharia Cooperatives, as well as contributing to the improvement of the economic well-being of the community.